Dynamic orientation transition of the lyotropic lamellar phase at high shear rates. Issue 48 (2nd October 2015) - Fujii, Shuji; Yamamoto, Yuki
Abstract : The dynamic orientation behavior of the lamellar phase of a triblock copolymer is studied in a wide range of shear rates as a function of solvent composition. Abstract : The dynamic orientation behavior of the lamellar phase of a triblock copolymer is studied in a wide range of shear rates as a function of solvent composition. We find that various phases can be induced by increasing the shear rate. At low shear rates, the onion phase forms from planar lamellae with many defects. A further increase of the shear rate caused the onion structure to break down, and the lamellar phase recovers with fewer defects. Finally, the transition of the orientation from parallel to perpendicular is observed at high shear rates. In the orientation transition at high shear rates, a stable intermediate structure, to our knowledge, is found for the first time. We also find that the critical shear stress of the rupture of the onion phase coincides with the orientation transition. The consistency of the critical shear stress suggests that all orientation transitions at a high shear rate are dominated by a mechanical balance between the applied viscous stress and the internal relaxation mode of the lamellae.